Metaphor - Donoghue, Denis (Harvard University Press, 2014)
Denis Donoghue turns his attention to the practice of metaphor and to its lesser cousins, simile, metonym, and synecdoche. Metaphor ("a carrying or bearing across") supposes that an ordinary word could have been used in a statement but hasn't been. Instead, something else, something unexpected, appears. The point of a metaphor is to enrich the reader's experience by bringing different associations to mind. The force of a good metaphor is to give something a different life, a new life. The essential character of metaphor, Donoghue says, is prophetic. Metaphors intend to change the world by changing our sense of it. At the center of Donoghue's study is the idea that metaphor permits the greatest freedom in the use of language because it exempts language from the local duties of reference and denotation. He also addresses the question of whether or not metaphors can ever truly die.--From publisher description